The effect of strategic fit between market orientation and supply chain orientation to supply chain performance - Yuhainis, Mohd Yusoff (2017)
Among the main issues discussed in supply chain management literature are the uncertainties and irrational behaviours. These issues are related to behavioural orientation that could affect supply chain performance. Previous studies on behavioural orientation in supply chain generally discuss the positive effects of a single strategic orientation rather than the alignments between several strategic orientations. Strategic approaches which are the alignments between orientations could enhance the relationship between strategic orientation and performance. Therefore, this study investigated the effect of alignments or FIT between market orientation and supply chain orientation to supply chain performance. This study also examined the mediating effect of supply chain management between strategic FIT and supply chain performance. Data were collected from manufacturers and suppliers among the players in the automotive industry in Malaysia through questionnaires. The Structural Equation Modeling (PLS-SEM) was employed to test the hypotheses. The results indicate that supply chain orientation and FlT are significantly related to supply chain performance. The results also show a strong prediction model that explains the mediation impact of supply chain management on supply chain performance except, only one relationship - market orientation and supply chain performance - is found insignificant. Therefore the objectives of this study that focus on the effect of FIT and SCM as a mediator are fulfilled. Thus, the insignificant result implies that companies including those protected by the government need to focus more on market orientation. To increase the research outcomes, future research could further explore the moderating effect of the environmental uncertainties and also the impact of all variables of company performance as part of the research framework